An Ecosystem Of Health Tourism In Penang - Nagindas, Shiladevi (2014)
Penang is fast becoming a hub for health tourism in the Northern Region of Peninsular Malaysia, with private hospitals tapping into this lucrative multi-million ringgit industry. This research is focused on Penang, which is the location of twenty percent of the thirty-five hospitals earmarked by the government to lead health tourism in the country. The main objectives of this research were to carry out a preliminary study to identify the characteristics of the health tourism industry in Penang; to identify and analyze the comparative advantages of private hospitals in Penang in being able to attract an increasing influx of health tourists in recent years; to evaluate the economic impact of health tourism in Penang; and to identify and analyze the strategies employed by these hospitals to compete and to experience further growth in the current global environment Two types of surveys were conducted: the hospital survey and the patient survey. The main instrument of data collection was the interview method, using questionnaires. Mixed methods of data analyses were employed to analyze and interpret the data. A unique combination of certain push factors in source areas and pull factors in Penang have given Penang the unique comparative advantage in attracting health tourists to its shores. The health tourism industry has led to the formation of important backward & forward linkages, and created significant spinoffs in terms of spillover effects and multiplier effects in the economy of Penang. Thus, the health tourism industry has a positive impact on Penang‟s economy and is a stimulus to its economic growth. However the industry faces intense competition, especially globally.